The Influence of Product, Process, and Business Model Innovation on Creative Entrepreneurship Performance in Developing Countries: The Moderating Role of Economic Uncertainty (Architecture Image Studies, 2025)
This study aims to analyze the effect of product, process, and business model innovation on creative entrepreneurial performance in developing countries, considering the moderating role of economic uncertainty. Using a quantitative approach, this study collected data from 250 creative entrepreneurs in Indonesia through a structured questionnaire. The results of a moderated multiple regression analysis show that all three forms of innovation have a significant positive effect on creative entrepreneurial performance. However, economic uncertainty acts as a negative moderator, weakening the relationship between innovation and performance. These findings contribute to the theoretical understanding of adaptation mechanisms of creative businesses in unstable economic environments, as well as offering practical implications for entrepreneurs and policymakers in designing effective innovation strategies amid uncertainty.